Market Entry Strategy for Paulaner Spezi in the Czech Republic : A 4P Marketing Mix Approach - Filipová, Markéta; Lhotáková, Markéta, 1971-; Král, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis presents a market entry strategy for Paulaner Spezi, a unique German cola-orange mix beverage, in the Czech Republic. It utilizes the 4P marketing mix framework—Product, Price, Place, and Promotion—to develop a tailored strategy that resonates with Czech consumer tastes and the local market landscape. Although cola-orange mix drinks are still quite new to Czech consumers, a nationwide survey involving over 7.000 respondents showed a strong interest in trying Paulaner Spezi, especially among younger, urban demographics. The research blends secondary data on market trends, buying habits, and competitive analysis with fresh survey insights about brand awareness, price sensitivity, packaging preferences, retail channel choices, and promotional impacts. From these insights, the thesis suggests launching Paulaner Spezi in 500 ml PET bottles and cans, with a price point between 26–35 CZK, and distributing it through supermarkets and discount stores. The promotional strategy should lean heavily on digital campaigns via Instagram and TikTok, complemented by in-store tastings and introductory discounts. The findings reveal a significant market opportunity for premium, differentiated soft drinks and show that a product like Paulaner Spezi can effectively attract Czech consumers through a strategy rooted in authenticity, accessibility, and experience-driven branding. The thesis wraps up with suggestions for future research, including product trials and regional segmentation analysis, to fine-tune the market entry strategy even further.
Vedoucí práce: Markéta Lhotáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses